INTERNET AND THE PROMOTION OF AQUACULTURE IN KENYA - Ndati, Ndeti; Okumu, Patel; Mogambi, Hezron (European Scientific Journal, ESJ, 2014)
The objective of this paper was to analyze the contribution of internet in the improvement of Aquaculture in Kenya and to establish the effectiveness of Phone internet in reaching the fish farmers. The paper further aimed at analyzing the role of Internet in the promotion of Aquaculture with particular reference to Kenya’s Ministry of Agriculture, Livestock and Fisheries fish Farming project. The target population was the Aquaculture farmers and officers from the Ministry of Agriculture, Livestock and Fisheries. The study used inferences from the population characteristics exhibited in the samples. One of the findings was that the computer, Internet and mobile phones ranked the highest in the most preferred ICT tools used in the promotion of aquaculture. According to the findings, 99 percent of the government officials had access to the Internet though the quality of internet service varied depending on the region. Some factors are also necessary to be considered in order to improve aquaculture information dissemination. Age, income and educational background of fish farmers should be considered while disseminating aquaculture information to them.